2007
DOI: 10.1177/1557988306293495
|View full text |Cite
|
Sign up to set email alerts
|

Fear, Knowledge, and Efficacy Beliefs Differentially Predict the Frequency of Digital Rectal Examination Versus Prostate Specific Antigen Screening in Ethnically Diverse Samples of Older Men

Abstract: Emotional and cognitive characteristics have been studied in the context of women's cancer screening but have received scant attention in the study of men's screening behavior. Researchers know little about how such factors interact to predict screening or whether digital rectal examination (DRE) and prostate specific antigen (PSA) screens are predicted by the same characteristics. This study examines the relevance of emotional and cognitive characteristics to DRE and PSA screening among 180 U.S.-born African … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
64
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 54 publications
5
64
0
Order By: Relevance
“…African Americans report greater fear of prostate cancer and screening, particularly for DRE (17,18), although there are exceptions (19). One study of 180 men found that both African American and Jamaican men reported greater screening fear than European Americans (20). In total, these studies suggest that minority men should report greater cancer worry and screening fear than U.S.-born European Americans.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…African Americans report greater fear of prostate cancer and screening, particularly for DRE (17,18), although there are exceptions (19). One study of 180 men found that both African American and Jamaican men reported greater screening fear than European Americans (20). In total, these studies suggest that minority men should report greater cancer worry and screening fear than U.S.-born European Americans.…”
Section: Introductionmentioning
confidence: 93%
“…Prostate-related anxiety may be caused by screening itself (45), men may avoid screening tests for fear of discovering prostate cancer (46,47), and concerns regarding discomfort or embarrassment may also be important (47,48). Men with greater state anxiety have been found to be more likely to drop out of a screening program (45), greater worry and concern about screening predicted self-care versus no care, although it was not related to conventional care (49), and screening fear predicted lower screening even when age, income, and education were controlled (20). Conversely, concern regarding prostate cancer has been associated with use of prostate-related complementary and alternative medicines (50) and greater trait anxiety predicted more frequent screening in a diverse group of men (27).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations